TECNOLOGIA ASSISTIVA PARA ALUNOS COM BAIXA VISÃO NAS ESCOLAS ESTADUAIS DE SÃO LUÍS: utilização na classe comum e na sala de recurso multifuncional - Gomes, Elayne Crystyna Pereira Borges (2015)
Assistive technology has been used in education with the main purpose of assisting people with disabilities, mainly in the inclusion process. Considering the teacher is a transforming agent who can perform innovative practices, supported by assistive technology, it is believed that the professionals working in education, students with low vision need to know this population and make use of assistive technology resources in order to facilitate the teaching and learning process of these students, providing development, transfer of knowledge according to the needs of each transformation into new knowledge, learning and training for social inclusion. Faced with this situation we realized the need to investigate the use of such Technology in the teaching-learning process of students with low vision in state schools in São Luís - MA, considering the importance of the issue for the whole society and contributions to the advancement of theme discussions. This research aims to investigate how Assistive Technology is being used by teachers in the educational care of students with low vision in common class and multifunctional resource room in state schools in São Luís. It is a quantitative and qualitative research, exploratory field and descriptive, with emphasis in the Case Study form. Semi-structured interview scripts were applied. The first one was carried out with six teachers from the regular classroom, working with students with low vision in state schools in São Luís - MA and the second one, with another teacher of multifunctional resource room all of which work with low vision student in a state school in Sao Luis - MA. Data collection took place between June 2015 and interviews were applied to six teachers from the regular class and another teacher of multifunctional resource room, which worked in the teaching-learning student process with low vision in the research school. Data analysis was based on assumptions of content analysis by comparative categorization of responses from participants. The results of this analysis revealed that participants have little understanding of the concept of Assistive Technology and use the source magnified as the main resource for the teaching-learning process of students with low vision. Participants were given guidance on the use of the resource, but not participated in the process of its implementation and choice. The difficulties experienced by the interviewed professionals in the use of Assistive Technology in the teaching-learning process of students with low vision include lack of resources; support; time; adequate training, among others. The main strategies identified by participants consisted of using large print and other resources; be much closer to the student; seek support of pedagogical coordination and use of own resources to perform the tasks. Regarding the adjustments in the use of Assistive Technology, the common class teachers do not perform any sort of adjustment, and the multifunctional resource room always performs in accordance with needs of student. Regarding the suggestions on the use of Assistive Technology in the learning process of students with low vision, participants mentioned the need for guidance and specific training; time to devote more; lack of family encouragement, among others. In our data, we conclude that for the use of Assistive Technology in teaching and student learning process with low vision is effective in state schools of São Luís. It takes planning of actions both in the regular classroom and in the resource room multifunctional; investment in teacher training; acquisition of new Assistive Technology resources; articulation between the school, maintenance of these resources by education department; cooperation between teachers of common class and multifunctional resource room for the learning is a motivating tool and encourage the individual to think independently through Assistive Technology resources, facilitating access to information and knowledge.